1986
DOI: 10.1002/cbf.290040103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of insulin receptors in isolated epithelial cells of rat ventral prostate: Effect of fasting

Abstract: Insulin receptors have been characterized in rat prostatic epithelial cells by using [125I]insulin and a variety of physicochemical conditions. The binding data at equilibrium (2 h at 15 degrees C) could be interpreted in terms of two populations of insulin receptors: a class of receptors with high affinity (Kd = 2.16 nM) and low binding capacity (28.0 fmol mg-1 protein), and another class of receptors with low affinity (Kd = 0.29 microM) and high binding capacity (1.43 pmol mg-1 protein). Proinsulin exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…But there has been little investigation into the role insulin itself plays in prostate cancer. Isolated epithelial cells of rat ventral prostate have insulin receptors, and fasting increases their concentration (Carmena et al, 1986). But PA-III rat prostate adenocarcinoma cells have no insulin receptor, though they do have specific binding sites for IGF-I and II (Polychronakos et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…But there has been little investigation into the role insulin itself plays in prostate cancer. Isolated epithelial cells of rat ventral prostate have insulin receptors, and fasting increases their concentration (Carmena et al, 1986). But PA-III rat prostate adenocarcinoma cells have no insulin receptor, though they do have specific binding sites for IGF-I and II (Polychronakos et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In our study LHhCG binding to Leydig cell was similar in fed and fasted rats, which also supports this hypothesis. The maintenance of normal insulin levels in interstitial fluid despite declining systemic insulin values in fasted rats is additional evidence that insulin levels found in the testis and especially in interstitial fluid are independent of plasma concentration [ 10, 181. Starvation has been associated with increased insulin binding to main targets [3] but also to the prostatic gland, which is not considered as a target tissue for insulin [9]. Leydig cells therefore appear to be an exception as regards to the starvation-related change of insulin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The present data together with previous results on the characterization of somatostatin-containing cells in the prostate gland [5,6] suggest a physiological involvement of the hormone acting in a local manner at this level. Furthermore, the increase of the number of hormones and neurotransmitters evoking a response from the cyclic AMP system [2][3][4] implies that the control of prostatic epithelial function may be exceedingly complex, involving not only androgens but also many other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory have shown that the prostatic cyclic AMP system is activated by a variety of agonists including classical neurotransmitters such as /Yadrenergic agonists [2] as well as more complex agents such as the neuropeptide vasoactive intestinal peptide (VIP) [3]. In contrast, the regulatory role of hormones or other factors negatively coupled to adenylate cyclase has not been as extensively investigated since only muscarinic receptors are known to lead to negative responses in this gland [4].…”
Section: Introductionmentioning
confidence: 99%